(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The analysis of the variants with double mark characteristics of the triple system, the supercomplex variants, indicates that it is not possible to generalize the use of this system to all the dental and velar syllabic signs, since for some of them the existence of the supercomplex variant is not even detected. Therefore, the triple system detected for ka and ke was probably a characteristic inherited, which would explain the existence of supercomplex variants in other signs, only as a relic. The fact that the supercomplex variants are also detected in Turdetan script, such as that of the sign ka, would also have as a more economic explanation that in both cases were an inherited feature from the original Palaeohispanic script, where it could be a general feature, rather than a double independent innovation.